Soviet Cultural Offensive - Barghoorn, Frederick C. (Frederick Charles), 1911-1991 (Book collections on Project MUSE., 1960)
The author has "tried to understand the realities of Soviet society, drawing both upon a superb critical judgment and a warmly sympathetic human insight." He "has given the American public material for thought and a prod in the right direction. "Originally published in 1960. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905